TPP AND CAREER DEVELOPMENT EFFECTS ON WORK BEHAVIOR THROUGH JOB SATISFACTION AT BKPSDM NATUNA - Anggoro, Mahesa Wirajati; Harianus; Shalahuddin, Ahmad; Daud, Ilzar; Sulistiowati; Komari, Nurul (Universitas Islam Negeri Alauddin Makassar, 2026)
Purpose – This study examines the effects of Employee Additional Income (TPP) and Career Development on Work Behavior through Job Satisfaction at BKPSDM Natuna. The study aims to explain how financial and non-financial factors influence employee behavior in the public sector. Methods – This study used a quantitative approach with PLS-SEM. Data from 51 respondents were collected through structured questionnaires using a census sampling technique and analyzed with SmartPLS to examine direct and indirect relationships among variables. Findings – The results reveal that TPP and Career Development significantly influence Job Satisfaction, while Job Satisfaction has the strongest effect on Work Behavior (β = 0.791). In addition, Job Satisfaction significantly mediates the effects of TPP and Career Development on Work Behavior. Research Implications – Although limited by its cross-sectional design and specific organizational context, this study provides practical implications for strengthening human resource management strategies to improve employee work behavior and organizational performance. Originality – This study emphasizes the important mediating role of Job Satisfaction, showing that indirect effects are stronger than direct effects in influencing Work Behavior. This research employs a quantitative approach with an explanatory research design. Data were collected from 51 employees of the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Natuna Regency using a census sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that TPP has a significant positive effect on both Job Satisfaction and Work Behavior, while Career Development significantly influences Job Satisfaction but not Work Behavior. Job Satisfaction does not directly affect Work Behavior but acts as a mediating variable. These findings suggest that financial incentives are the primary driver of employee behavior, while career development contributes indirectly through enhancing job satisfaction.